1970
DOI: 10.3329/bjb.v37i1.1556
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of agronomic characters of <i>Festulolium</i>, <i>Festuca pratensis</i> Huds. and Lolium multiflorum Lam. genotypes under high elevation conditions in Turkey

Abstract: Prior {Lolium perenne × Festuca pratensis) and Elmet (Lolium multiflorum × Festuca pratensis) cultivars were compared with Festuca pratensis Huds. and Lolium multiflorum Lam. genotypes for some agronomical characteristics (green and dry matter yields, crude protein, seed yield, crude ash content) under Erzurum ecological conditions. Analysis of variance and mean separation were performed using the SPSS 11.0 computer program. There was a significant difference among genotypes in every character tested except fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…A stubble height of around 15 cm is considered as the practical minimum harvest height for most growers in Europe (Bitarafan and Andreasen, 2020c). Problematic grass weed species in Europe such as A. myosuroides, A. spica-venti and L. multiflorum are tall growing (>80 cm) upright plants with erect seed heads, making it possible to capture the retained seeds with the harvester (CABI, 2021a, Akhter et al 2020a, Akgun et al, 2008.…”
Section: Prerequisites For the Success Of Hwscmentioning
confidence: 99%
See 1 more Smart Citation
“…A stubble height of around 15 cm is considered as the practical minimum harvest height for most growers in Europe (Bitarafan and Andreasen, 2020c). Problematic grass weed species in Europe such as A. myosuroides, A. spica-venti and L. multiflorum are tall growing (>80 cm) upright plants with erect seed heads, making it possible to capture the retained seeds with the harvester (CABI, 2021a, Akhter et al 2020a, Akgun et al, 2008.…”
Section: Prerequisites For the Success Of Hwscmentioning
confidence: 99%
“…In Northern Europe, L. multiflorum is causing significant yield losses in winter cereal crops. The fact that L. rigidum and L. multiflorum retain a significant number of seeds until harvest in wheat, indicates that HWSC has potential to manage these two species (Akgun et al, 2008;Blanco-Moreno et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Festulolium is one of the most resistant and productive species among perennial grasses, especially during the seasons characterized by unfavorable weather conditions. It is a promising crop that meets the high requirements imposed on species being used for creating a high-quality fodder base [1,6,20].…”
Section: Introductionmentioning
confidence: 99%
“…However, in Europe, the cultivation of new species on larger areas started after 2010 (Østrem et al, 2013). Such studies have shown that Festulolium has a higher potential for green fodder, dry matter and seed yields compared to its parents (L. multiflorum and F. pratense) (Akgun et al, 2008). Festulolium also showed good adaptability to the external environment conditions (Abdelhalim 2016;Humphreys et al, 2013Humphreys et al, , 2014.…”
Section: Introductionmentioning
confidence: 99%